2019
DOI: 10.1002/bmc.4698
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and UHPLC–DAD detection of undeclared substances in market‐available dietary supplements and slimming products in Eastern region, Saudi Arabia: An application of principal component analysis

Abstract: Background Dietary supplements (DS) containing undeclared substances may pose serious risk to s public health. The consumers of DS should be aware of such products in order to avoid the risk of fatal outcomes. Aim of the study The study is based on the determination and identification of undeclared substances – theobromine (TB), theophylline (TH), pseudoephedrine (PE), caffeine (C), hydrochlorothiazide (HTZ) and yohimbine (Y) – in market‐available DS. Material and methods Ultra‐high‐performance liquid chromato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 25 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…Theophylline (1,3-dimethylxanthine, TP) is a purine alkaloid that is found in the three most popular ingredients in the world: tea, coffee, and cocoa . There are reportedly about 1.8 mg/g TP in tea leaves, 0.04 mg/mL in black coffee, and 2.0 mg/g in cocoa powder . Previous studies have revealed that TP exhibits good biological activities, such as the abilities to diuresis and natriuresis, excite the central nervous system, stimulate lipolysis, and resist inflammation .…”
Section: Introductionmentioning
confidence: 99%
“…Theophylline (1,3-dimethylxanthine, TP) is a purine alkaloid that is found in the three most popular ingredients in the world: tea, coffee, and cocoa . There are reportedly about 1.8 mg/g TP in tea leaves, 0.04 mg/mL in black coffee, and 2.0 mg/g in cocoa powder . Previous studies have revealed that TP exhibits good biological activities, such as the abilities to diuresis and natriuresis, excite the central nervous system, stimulate lipolysis, and resist inflammation .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the development and consumption of dietary supplements from edible and medicinal plants have become very popular globally. Dietary supplements are products used to supplement nutritional components such as proteins, vitamins, minerals, botanical compounds, and probiotics (Ahmad et al, 2020). Many plants are used as dietary supplements to prevent and treat obesity, including green tea, ginger, aloe vera, and lingonberry (Liu et al, 2019;Shang et al, 2021;Si et al, 2021).…”
Section: Potential Plant Species For the Formulation Of Anti-obesogen...mentioning
confidence: 99%
“…More importantly, a loophole exists to establish an adulteration markers procedure for the final products. Reishi is prone to contamination with other species as the herbal products/dietary supplements now‐a‐days have been reported to contain a variety of hidden or banned drugs (Ahmad, Ahmad, AlHudaithi, et al, 2020b). Blood‐brain barrier (BBB) and Reishi ; the literature claims the effect on cognitive function and anti‐Alzheimer's potential for Reishi.…”
Section: Critical Assessment and Future Perspectivesmentioning
confidence: 99%